2008
DOI: 10.1002/cncr.23318
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of apoptosis resistance and treatment strategies to overcome them in hormone‐refractory prostate cancer

Abstract: New therapeutic strategies are needed to improve treatment outcomes in men with hormone-refractory prostate cancer. A better understanding of the molecular mechanisms of cell death in response to therapeutic strategies will help avoid ineffective treatment regimens and provide a molecular basis for new therapeutic modalities targeting apoptosis-resistant forms of prostate cancer. In this review, the authors focused on the established aberrations of apoptosis in hormonerefractory prostate cancer, and they have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…43 Hsp27 has been reported to be elevated in many human tumors and is a predictor of poor clinical outcome (androgen-independence), as it has a cytoprotective role by interfering with many key regulators of apoptosis. 37,44 Multiple RTKs, Bcl-2 and Hsp27 have all been implicated in hormone resistance, 41,45,46 and we have shown that Reg IV modulates the spectrum, therefore suggesting that a Reg IVtargeted therapy could have utility in drug resistant patient populations. In addition to expanding our understanding of signaling downstream of Reg IV, our results support a potential therapeutic benefit in neutralizing Reg IV activity in Reg IV-positive patient populations.…”
Section: Cancer Cell Biologymentioning
confidence: 84%
See 1 more Smart Citation
“…43 Hsp27 has been reported to be elevated in many human tumors and is a predictor of poor clinical outcome (androgen-independence), as it has a cytoprotective role by interfering with many key regulators of apoptosis. 37,44 Multiple RTKs, Bcl-2 and Hsp27 have all been implicated in hormone resistance, 41,45,46 and we have shown that Reg IV modulates the spectrum, therefore suggesting that a Reg IVtargeted therapy could have utility in drug resistant patient populations. In addition to expanding our understanding of signaling downstream of Reg IV, our results support a potential therapeutic benefit in neutralizing Reg IV activity in Reg IV-positive patient populations.…”
Section: Cancer Cell Biologymentioning
confidence: 84%
“…Currently, there is an unmet need for treating patients with metastatic prostate and colorectal cancers. With respect to metastatic prostate cancer, hormone ablation is common but most men eventually develop androgen-independence, 41 and current chemotherapy for hormone refractory prostate cancer has yielded survival rates of only 12 months. 42 Some molecules have been reported to play a key role in hormone resistance.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…[1][2][3][4][5][6] Within the PCa-derived cell lines studied, androgen-independent PC3 cells are previously shown to be moderately sensitive, and LNCaP cells are reported to be resistant to TRAIL-induced apoptosis. [11][12][13][14][15][16][17][18][19][20] Given the established role of ethanol in inducing cell death, it is a promising agent for promoting tumor cell death in combination with known therapeutic drugs such as TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) induces apoptosis in a broad range of cancer cells, with little or no effects on normal cells. [7][8][9][10] Within the PCa-derived cell lines studied, there is extensive variability in their sensitivity to TRAIL-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is the predominant form of tumor cell demise caused by chemotherapeutic agents and it plays an important role in cancer chemosensitivity and radiosensitivity (Arnold & Isaacs, 2002;Debes & Tindall, 2004). Targeting various mechanisms of apoptosis to cure prostate cancer has been suggested in many studies, naming potential molecular targets and key apoptotic regulators such as upstream and downstream caspases, p53, Phosphatase and tensin homolog (PTEN), prostate apoptosis response gene-4 (Par-4), Bcl-2 (B-cell lymphoma 2) protein, transcription factor NF-kappa B, serine/threonine protein kinase and others (Uzzo et al, 2008;Wang et al, 2004). Precisely, manipulating with sensitivity to cytotoxic agents to alter cancer progression has been suggested as a therapeutic approach for prostate cancer in some reports (McKenzie & Kyprianou, 2006;Watson & Fitzpatrick, 2005).…”
Section: Introductionmentioning
confidence: 99%